Enhancing organizational citizenship behavior: The influence of job crafting and employee well-being - Rurkkhum, Suthinee (Kasetsart Journal of Social Sciences, 2026)
In light of a post-pandemic future, there is a crucial need to devise suitable strategies to maintain positive emotions in the workplace because employees who feel positive emotions at work can improve their performance and pay it forward. This study hypothesized that the positive effect of job crafting can relate to psychological and behavioral aspects. Drawing on the broaden and-build theory, this study examined the mediating effect of employee well being on the relationship between job crafting and organizational citizenship behavior (OCB) among 317 Thai employees in an insurance company. A partial mediating role of employee well-being was detected. Job crafters can experience well-being and engage in OCB as a result of positive emotions. A highly uncertain environment requires employees to adapt and take an active role in expanding their behavior, emphasizing the importance of the concept of OCB. This study indicated that an organization can increase the level of OCB among employees by stimulating them to craft their jobs to experience positive emotions and well-being. This study thus highlighted the significance of fostering positive emotions at work, particularly in non-western settings and challenging times.